Technical feasibility for pilot scale production of candied kalamansi (Citrus Microcarpa, Bunge) peel - Batulan, Genoveva B. (1977)
The approach of the study included the determination of the length of boiling time and the number of boiling water changes of the peels; standardization of the amount of food color to be used; determination of the optimum plumping time; establishment of the length of time of the drying process; and the determination of the level of ascorbic acid needed for fortification. Results indicate that a ten-minute boiling time with four changes of boiling water were the combinations found best to debitter the peels. The optimum amount of food color was 0.15% by weight of the peels. The average equilibrium plumping time was three hours. Drying the candied peels for 7 hours in the cabinet dryer produced a chewy but firm texture. Sundrying the peels for 24 hours gave a similar characteristic. Separately incorporating 50, 60 and 70 mg of ascorbic acid dissolved in Karo Crystal Clear Syrup and the final candying syrup into 100 mg of peels resulted in similarly low percentage retentions. The highest value observed was 41% retention for the sun-dried candied product 70 mg/100 g peel and to which 0.1% of Vitamin C was added. The pilot scale product was similar to those produced by laboratory scale. This was characterized subjectively as appealing, with firm-chewy texture, and acceptable olive-green color and a flavor characteristically kalamansi.